Optimizing the Collaboration Between MSMEs and Digital Marketplaces: Innovative Strategies to Enhance Market Expansion and Business Sustainability in the Digital Economy Era - Yani, Ahmad; Mustafa, Fahrina; Santosa, Sonny (PT. LITERASI SAINS NUSANTARA, 2025)
The rapid growth of digital transformation has urged Micro, Small, and Medium Enterprises (MSMEs) to adapt by leveraging digital marketplace platforms as a primary strategy for expanding their market reach and maintaining business sustainability. This study is a literature review employing a qualitative approach and descriptive analysis to explore how strategic collaboration between MSMEs and digital marketplaces can be optimized within the context of Indonesia's digital economy. Data were collected from 35 scholarly articles and credible sources published between 2014 and 2025, with a strict selection process narrowing them down to 17 relevant articles for analysis. The results indicate that synergistic and innovative collaborations with digital platforms such as Tokopedia, Shopee, and GrabFood significantly contribute to market expansion, operational efficiency, and the strengthening of MSME brand identities. Case studies including Brodo, Kopi Kenangan, and Maicih illustrate successful collaborative practices through digital features, data-driven promotion, and continuous training. These findings highlight the importance of digital literacy, strategic planning, and cross-sectoral support in building an inclusive and sustainable digital ecosystem for MSMEs in Indonesia.